Prevalence and associated factors of overweight and obesity among Afghan school children: A cross-sectional analytical study from Kandahar City, Afghanistan - Bilal Ahmad Rahimi; Aziz Ahmad Khalid; Wahid Ahmad Khalid; Javed Ahmad Rahimi; Walter R. Taylor (PLoS ONE, 2025)
Background Childhood overweight and obesity is an emerging public health problem in developing countries. This is the first school-based study of its type from Afghanistan to estimate the prevalence and associated factors of overweight and obesity among Afghan school children aged 6–18 years in Kandahar City of Afghanistan. Methods This cross-sectional analytical study was conducted among 2281 school children from January 10–April 15, 2024. Sociodemographic properties, anthropometric measurements, and other data were collected from all the participants. Data were analyzed using descriptive statistics, Chi-square test, and multiple logistic regression analysis. Results Among the 2281 enrolled children, 72.5% were boys, 65.1% going to private schools, and 53.8% poor. The prevalence of overweight and obesity was 11.5% (6.6% were overweight and 4.9% were obese). The mean (SD) age was 12.7 (2.1) years. By logistic regression analysis, statistically significant risk factors associated with overweight and obesity were being boy (AOR 1.5 and 95% CI 1.1–2.0), student of private school (AOR 2.2 and 95% CI 1.5–2.8), belonging to a rich family (AOR 1.9 and 95% CI 1.3–2.7), and parental obesity (AOR 1.5 and 95% CI 1.1–2.0). Conclusion School children of Kandahar city are suffering from overweight/obesity. Overweight/obesity should be dealt with as an emerging problem in school children of Kandahar city. It is recommended that Afghanistan ministries of education and public health, with the help of international donor agencies, such as WHO and UNICEF, work together in controlling overweight and obesity in school children of Kandahar city. Periodic special awareness programs on the prevention and control of overweight/obesity should be conducted in schools, radio, television, and other sources of social media.